Probiotic survival during a multi‐layered tablet development as tested in a dynamic, computer‐controlled in vitro model of the stomach and small intestine (TIM‐1). (9th October 2019) - Venema, K.; Verhoeven, J.; Verbruggen, S.; Espinosa, L.; Courau, S.
Abstract: The aim of the research was to develop a galenical formulation for the combination of the three probiotic strains Lactobacillus gasseri PA 16/8, Bifidobacterium longum SP 07/3 and Bifidobacterium bifidum MF 20/5 that would lead to the presence of a high amount of viable cells in the small intestine, the presumed site of action of these strains. This was tested in a validated, dynamic in vitro model of the stomach and small intestine (TIM‐1), simulating human adults after intake of a meal. Experiments were performed both in the gastric compartment of the model, as well as in the complete system (stomach + small intestine). Survival of the strains in an unformulated probiotic powder after transit through the gastric compartment was 5·3% for the bifidobacteria and 1% for L. gasseri . After transit through the complete gastrointestinal tract, this dropped to 2% for bifidobacteria and 0·1% for Lactobacillus . After several rounds of optimization, an enteric‐coated tablet was developed that increased the delivery of viable cells reaching the small intestine to 72% (gastric survival) for bifidobacteria, and 53% (gastric) for L. gasseri . Also survival in the small intestine increased by about an order of magnitude. The final galenical formulation was tested in two applications: adults and elderly, both of which have their own physiological parameters. These experiments corroborated the results obtained in the development phase of the project. In conclusion, the developed enteric coating led to a 20‐ to 40‐fold increase in the delivery of viable cells to the small intestine. Significance and Impact of the Study: Predictive GI in vitro models are very helpful and reliable tools for the development of new galenical formula containing probiotics, and in the current example helped to deliver >10‐fold higher numbers of viable cells to the small intestine, presumably leading to improved functionality of the strains. Abstract : Significance and Impact of the Study: Predictive GI in vitro models are very helpful and reliable tools for the development of new galenical formula containing probiotics, and in the current example helped to deliver >10‐fold higher numbers of viable cells to the small intestine, presumably leading to improved functionality of the strains.